Public administration and policy making:the political/career executive environment - Lorentzen Paul B.
Federal government policy making is improved by the participation of career executives. As a minimum, contributions based on their professional expertise and institutional experience can serve as an early warning system for helping political executives to avoid mistakes in new policy ventures. However, a number of political, structural, and attitudinal factors cause the political/career executive relationship environment to be characterstically stressful, tense, and frequently not conducive to joint involvement in policy making. Historic factors producting this environment include basic constitutional and democratic values regarding the exercise of unitary power, the ambigouous roles of political and career ex
Keywords: Career Service -- U.S.A.; Bureaucracy -- U.S.A.; Executives -- U.S.A.